2012
DOI: 10.1038/tp.2012.96
|View full text |Cite
|
Sign up to set email alerts
|

The association of attempted suicide with genetic variants in the SLC6A4 and TPH genes depends on the definition of suicidal behavior: a systematic review and meta-analysis

Abstract: The global prevalence of suicide has increased substantially over the last four decades. Suicidal behavior manifests owing to a combination of biological, behavioral and social factors; however, the etiology of suicidality remains elusive. Even though twin studies have reported a significant heritability of 30–50%, meta-analyses have not highlighted a common genetic variant associated with the spectrum of suicidal behavior. Here, we performed a systematic review of the literature (n=112) to assess the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 36 publications
6
39
0
3
Order By: Relevance
“…Considering the different suicidal phenotypes, including a review of related meta-analyses, the s allele seems to be associated with impulsive and aggressive suicidal behaviours and completed suicide (Bondy et al 2000) and violent (Bayle et al 2003;Bellivier et al 2000;Courtet et al 2001) as well as repeated suicide attempts (Courtet et al 2004). A recent meta-analysis suggests that 5HttLPR and the RS1800532 (tryptophan hydroxylase variant) polymorphisms are significantly associated with suicide attempts, but not associated with completed suicides (Clayden et al 2012).…”
Section: Serotonin Transporter Imaging and Post-mortem Studies Of Suimentioning
confidence: 99%
“…Considering the different suicidal phenotypes, including a review of related meta-analyses, the s allele seems to be associated with impulsive and aggressive suicidal behaviours and completed suicide (Bondy et al 2000) and violent (Bayle et al 2003;Bellivier et al 2000;Courtet et al 2001) as well as repeated suicide attempts (Courtet et al 2004). A recent meta-analysis suggests that 5HttLPR and the RS1800532 (tryptophan hydroxylase variant) polymorphisms are significantly associated with suicide attempts, but not associated with completed suicides (Clayden et al 2012).…”
Section: Serotonin Transporter Imaging and Post-mortem Studies Of Suimentioning
confidence: 99%
“…Association studies have revealed several alleles conferring an increased risk of suicidal behavior, although each variant taken individually usually yields a small effect size [21]. In the particular case of small endogamous groups, seminal conditions of genetic drift in one group -for instance a founder effect (a group born from a small number of founders) or a bottleneck (the reduction in the size of the population at one point of its history, following a natural disaster or an epidemic for instance) -may have initially led to the selection of risk alleles at a frequency superior from what is found in the original population [22].…”
Section: Discussionmentioning
confidence: 99%
“…18 El fenotipo de intento suicida es altamente heterogéneo, por lo que analizar rasgos asociados con dicha conducta permite tener características más homogéneas que ayuden a encontrar los genes de susceptibilidad para el desarrollo de conductas tan complejas como el suicidio, como lo demuestra el metaanálisis de Clayden, el cual reporta que no existe correlación entre los polimorfimos genéticos y la conducta suicida en general; sin embargo encuentra una asociación significativa entre los subgrupos de personas con intento suicida y el gen transportador de serotonina 5-HTTLPR. 16 Por otra parte, el análisis de las características clínicas mostró un hallazgo interesante en los pacientes portadores del genotipo "SS", los cuales presentaron una mayor gravedad de desesperanza. Este hecho apoya los datos que muestran que los pacientes con este síntoma presentan un mayor riesgo de tener intento suicida.…”
Section: Discussionunclassified